Survei tingkat penalaran ilmiah peserta didik se-SMA Negeri Tangerang Selatan - Fadlilah, Dina Rahma; Fauziah, Ayu Syifa; Miranto, Sujiyo (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The scientific reasoning skill in Indonesia is still considered low and research is rarely done, whereas in addition to having a long-term impact on cognitive development and academic achievement, scientific reasoning skill also prepares students to be able to compete in the global era. The importance of scientific reasoning skill also listed in Permendikbud Nomor 64 Tahun 2013 and Permendikbud Nomor 21 Tahun 2016. This descriptive study aims to describe the scientific reasoning skill of high school students in South Tangerang and obtain information about the importance of scientific reasoning skill. This research was conducted at 6 high schools in South Tangerang City based on cluster random sampling. The instrument used was a description test using the material of the circulatory system based on 5 Karplus scientific reasoning patterns that were developed, then the results of the tests were categorized based on the level of scientific reasoning. The results of this study are the Serial Ordering pattern 15.26%, Class Inclusion Reasoning 11.7%, Correlational Reasoning 8.57%, Theoretical Reasoning 6.28% and Functionality Reasoning 6.75%, and the category of scientific reasoning ability from all schools at the transition level.